High-quality RNA extraction and the regulation of genes encoding cellulosomes are correlated with growth stage in anaerobic fungi - Brown, Jennifer L.; Gierke, Taylor; Butkovich, Lazarina V.; Swift, Candice L.; Singan, Vasanth; Daum, Christopher; Barry, Kerrie; Grigoriev, Igor V.; O’Malley, Michelle A. (Frontiers in Fungal Biology, 2023)
Anaerobic fungi produce biomass-degrading enzymes and natural products that are important to harness for several biotechnology applications. Although progress has been made to develop methods that extract nucleic acids for genomic and transcriptomic sequencing of these fungi, most studies are limited in that they do not sample multiple fungal growth phases in batch culture. In this work, we establish a method to harvest RNA from fungal monocultures and fungal-methanogen co-cultures, and also determine an optimal timeframe for high-quality RNA extraction from anaerobic fungi. Based on target RNA quality and quantity targets, the optimal range for RNA harvest in anaerobic fungal monocultures and fungal-methanogen co-cultures was 2-5 days of growth post-inoculation. When cultivated on cellulose, the fungal strain Anaeromyces robustus co-cultivated with the methanogen Methanobacterium bryantii upregulated genes encoding fungal carbohydrate active enzymes and other cellulosome components relative to fungal monocultures during this timeframe, but expression patterns changed at 24-hour intervals throughout the fungal growth phase. These results demonstrate the importance of establishing methods to extract high-quality RNA from anaerobic fungi at multiple timepoints during batch cultivation.